The Sombor Indices of Banana Tree Graph and Fractal Tree Type Dendrimer - Rajeswari K, Thanga; A, Manimaran (Contemporary Mathematics, 2024)
Topological descriptors are graph-theoretical metrics that allow one to describe a molecular structure’s underlying connectedness. Degree-based topological descriptors have been investigated widely and are associated with several chemical characteristics. The examination of graph entropy indices as a gauge for the intricacy of the underlying connection and as a means of characterizing structural attributes has also gained significance.The present study utilizes the graph-theory-based edge partition method to examine Sombor variants for the Banana Tree Graph, Fractal, and Cayley Tree Type Dendrimers. We have employed Shannon’s entropy model to determine the graph-based entropy of these graphs and produced Sombor indices.